Theoretical study on the conformation-dependent charge transfer of the excited state of dopamine - Huan An; Asiya; Gulmire Yaermaimaiti; Bumaliya Abulimiti; Mei Xiang; Xiaoning Wang (Heliyon)
Clarifying the relationship between conformation and charge transfer is crucial for understanding the functional mechanisms of molecules in organisms. Theoretical calculations of dopamine, N,N-dimethyldopamine, and N,N-dihydroxydopamine were related to conformation and charge transfer, and the charge transfer of the excited state was clearly characterized. First, the stable configuration of the ground state of the molecule was optimized, and the potential energy of the ionic state was scanned to select all conformations, except for the chiral problem. Subsequently, the CAM-B3LYP/aug-cc-pVTZ method was used to excite the molecule, and the excitation types of the first five excited states of the molecule were discussed. Finally, the charge transfer of the molecule was calculated, and the charge transfer of the different conformations was analyzed in detail. Through charge transfer, it has been speculated that dopamine molecules exist in a coiled state in an organism and interact with water to form N,N-dihydroxydopamine, or hydrogen bonds for better information transmission.